Prognostic awareness in family caregivers of patients with terminal illness: a scoping review - Stefano Terzoni; Paola Arcadi; Ilaria Bovi; Mariachiara Figura (BMJ Open)
Objective To map and synthesise the existing literature on the prognostic awareness of family caregivers of terminally ill patients with advanced disease.Design Scoping review following the Joanna Briggs Institute methodology and Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines.Data sources A comprehensive search was conducted in six nursing and healthcare databases: CINAHL, Cochrane, ILISI, PubMed, PsycINFO and Scopus. The literature search was conducted in August 2024 without date limitations.Eligibility criteria Research studies of any design focusing on prognostic awareness in family caregivers of patients with terminal illness were included. Studies were included if they were published in English, Spanish or Italian. Reviews, editorials and grey literature were excluded.Data extraction and synthesis Two reviewers independently screened and selected studies, extracted data and charted results. A descriptive synthesis was performed to summarise study characteristics, conceptual definitions of PA, measurement approaches and main findings.Results 18 studies were included, highlighting four main themes and related subthemes. (1) Factors influencing caregivers’ prognostic awareness: these include caregiver-specific factors (eg, sociodemographic characteristics, relationship with the patient, emotional burden), caregiving context (eg, patient’s trigger events, healthcare settings) and communication dynamics (eg, delays, insufficient communication, tailored approaches). (2) Prognostic concordance: discordance among patients, caregivers and healthcare providers is common and linked to miscommunication, emotional unpreparedness and differing treatment goals. (3) Outcomes of prognostic awareness: accurate awareness facilitates palliative care decisions and improves patient quality of life but may increase caregiver stress and depressive symptoms when emotional preparedness is lacking. (4) Evolution of prognostic awareness: awareness evolves with illness progression but fluctuates based on emotional and cognitive adaptation.Conclusions Caregivers’ prognostic awareness is critical to end-of-life care planning, facilitating transitions to palliative care and reducing unnecessary aggressive treatments. However, it also poses psychological challenges for caregivers, highlighting the need for tailored communication strategies and emotional support.